DIGITALISASI TRANSAKSI DAN REBRANDING PRODUK: IMPLEMENTASI E-POS DAN DESAIN KEMASAN PADA UMKM TEMPOYAK MAK SYALU, PALEMBANG - Ummy Gusti Salamah; Kamilia Syaputra; Yulia Hapsari; Nia Sahbellah; Rio Adrian; Fakhri Irawan (Universitas Mataram, 2025)
This community service program aims to enhance the operational efficiency and competitiveness of UMKM Tempoyak Mak Syalu through the implementation of the Electronic Point of Sales (E-POS) system for transaction digitalization and product rebranding via new packaging design and social media optimization. The activity was conducted over three days in July and continues to be implemented at UMKM Tempoyak Mak Syalu, Palembang, using methods such as training, technical assistance, and direct implementation of the E-POS system along with product packaging innovation. Evaluation was carried out through observation, interviews, and measurement of key performance indicators, including transaction input time, recording error rate, sales volume, and digital promotion effectiveness. The results show a significant improvement in efficiency, with transaction recording time reduced from an average of 10–15 minutes to 3–5 minutes per day (approximately 60% more efficient) and a 78% reduction in input errors. The E-POS system also facilitated stock management and automated financial reporting. On the marketing side, the introduction of new packaging and professional product photography enhanced brand clarity and consumer trust, leading to a 50% increase in monthly sales. This program demonstrates that transaction digitalization and product rebranding effectively strengthen the digital literacy of small business owners, improve operational efficiency, and expand market reach through more professional digital branding.